The sequence of the nucleoprotein gene of human influenza A virus, strain A/NT/60/68. - Huddleston, J A (1982)
The nucleotide sequence of the nucleoprotein gene of influenza A/NT/60/68 was established after using improved cloning methods to obtain full length cDNA clones in pBr322. The gene is 1565 residues long and codes for a basic protein of 498 amino acids. There are only 30 amino acid differences between it and the homologous sequence in A/PR/8/35, all occurring as point mutations. Assuming a common lineage, the evolutionary rate of divergence of the two strains is 0.18% amino acid per year. This confirms there is a slow but significant rate of evolution.